Establishing and strengthening farmers organizations - S.K. Santra,; B. Haldar, (Journal of Agricultural Extension Management, 2025)
Historically, extension has mainly involved technology transfer, with the village extension worker (VEW) transferring knowledge from research stations to farmers by using individual, group and mass media methods. More recently, extension has been asked to play a "Technology development role" by linking research with community group needs and helping to facilitate appropriate technology development. It is in the historical context that many government agencies developed national polices for rural development and designed a policy framework to help rural people become organized so that the delivery of services could be channelled through various types of farmer organizations or groups. Well-meaning policies also provided blue-print structures for farmer organizations (FO) in the form of co-operatives and commodity organizations in order to provide various input making and educational services to the farmers